2016
DOI: 10.1111/are.12957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary chitosan oligosaccharide complex with Ce (IV) on growth, immunity and disease resistance againstVibrio splendidusof sea cucumber,Apostichopus japonicas

Abstract: An 8-week feeding trial was conducted to investigate the effects of dietary chitosan oligosaccharide complex with cerium (Ce IV) (COS-Ce) on growth performance, nonspecific immunity and disease resistance of sea cucumber, Apostichopus japonicas. Five isonitrogenous (18.6%) and isolipidic (1.1%) practical diets were formulated with graded level of COS-Ce (0, 150, 300, 600 and 1200 mg kg À1 dry feed), which were named as COS-Ce/0, COSCe/150, COS-Ce/300, COS-Ce/600, COS-Ce/1200 respectively. Each diet was allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Oral administration of dietary chitosan has been shown to increase the growth performance of weaned pigs [ 47 ], tiger puffers [ 48 ], sea cucumbers [ 49 ], Japanese quail [ 50 ], turbot [ 51 ], Japanese koi [ 52 ], and loaches [ 26 ]. In the current work, the dietary chitosan-treated formulated feed positively improved body weight gain, %BWG, and SGR compared with those of the control group, while FCR exhibited the opposite trend.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of dietary chitosan has been shown to increase the growth performance of weaned pigs [ 47 ], tiger puffers [ 48 ], sea cucumbers [ 49 ], Japanese quail [ 50 ], turbot [ 51 ], Japanese koi [ 52 ], and loaches [ 26 ]. In the current work, the dietary chitosan-treated formulated feed positively improved body weight gain, %BWG, and SGR compared with those of the control group, while FCR exhibited the opposite trend.…”
Section: Discussionmentioning
confidence: 99%
“…At each stage of the challenge test, the lowest values of pathogenic bacteria among all treatments invariably appeared in the LT group, suggesting that the LT group was more efficient at removing pathogenic bacteria in intestines. It may be reasonably inferred from the results that the application of L. acidophilus and TIS in combination could induce bacterial antagonism by producing antimicrobial agents that could neutralize the negative effects of pathogenic bacteria (Newaj & Austin, 2015;Wang et al, 2017). However, the antibacterial mechanism of sea cucumbers to V. splendidus after F I G U R E 5 (a) Distribution of gut microbiota on phylum level in four groups just after the feeding trial and (b) after 3 d of V. splendidus challenge [Colour figure can be viewed at wileyonlinelibrary.com] probiotics and immunostimulants treatments remains incompletely explained and further extensive testing is necessary.…”
Section: Resistance To Pathogenic Bacteriamentioning
confidence: 99%
“…POD is an enzyme of oxidation resisting and is able to protect the host from reactive oxygen compounds that are produced by the host to kill invasive pathogens (Wu and Yi, ; Zhang et al ., ; Wang et al . ). Zang et al .…”
Section: Discussionmentioning
confidence: 97%
“…It is known that the innate immune system responds faster than the adaptive immune system during pathogen infection. POD is an enzyme of oxidation resisting and is able to protect the host from reactive oxygen compounds that are produced by the host to kill invasive pathogens (Wu and Yi, 2015;Zhang et al, 2015;Wang et al 2017). Zang et al (2017) found that the POD activity of zebrafish (Danio rerio) significantly increased after 7-day postexposure to boscalid.…”
Section: Discussionmentioning
confidence: 99%